2014
DOI: 10.1097/mpg.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Endpoints and Clinical Outcome Assessments in Pediatric Ulcerative Colitis Registration Trials

Abstract: Pediatric-specific endpoints were used, but outcome measures and definition of clinical response were not consistent in pediatric UC trials. Consensus on the definition of successful treatment outcome (clinical response and/or remission) and collaboration in the development of well-defined and reliable measures of signs and symptoms for use in conjunction with endoscopic parameters of mucosal healing will facilitate pediatric drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Recently, physicians at regulatory agencies have suggested that the PUCAI may not be an optimal measure of disease activity in clinical trials[8]. The PUCAI is a clinician reported outcome rather than patient reported outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, physicians at regulatory agencies have suggested that the PUCAI may not be an optimal measure of disease activity in clinical trials[8]. The PUCAI is a clinician reported outcome rather than patient reported outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge encountered with these conditions is that the pathophysiology is often less well-understood and pediatric validated clinical endpoints are often lacking. 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…However, consensus on the definition of successful treatment outcome (clinical response and/or remission) and col-laboration in the development of well-defined and reliable measures of signs and symptoms for use in conjunction with endoscopic parameters of mucosal healing has become necessary to facilitate pediatric IBD drug development [12]. Endoscopy in pediatric IBD provides a more definitive diagnosis and disease extent evaluation, assesses therapeutic efficacy, and leads to a targeted therapy [13].…”
Section: Clinical Outcome Assessmentmentioning
confidence: 99%